2010
DOI: 10.1002/etc.175
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccumulation kinetics of organic xenobiotic pollutants in the freshwater invertebrateGammarus pulexmodeled with prediction intervals

Abstract: Uptake and elimination rate constants, bioaccumulation factors, and elimination times in the freshwater arthropod Gammarus pulex were measured for 14 organic micropollutants covering a wide range of hydrophobicity (imidacloprid, aldicarb, ethylacrylate, 4,6-dinitro-o-cresol, carbofuran, malathion, 4-nitrobenzyl-chloride, 2,4-dichloroaniline, Sea-Nine, 2,4-dichlorophenol, diazinon, 2,4,5-trichlorophenol, 1,2,3-trichlorobenzene, and hexachlorobenzene; all 14C-labeled). The toxicokinetic parameters were determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
119
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(125 citation statements)
references
References 70 publications
5
119
1
Order By: Relevance
“…The relatively large BCF of 51.5 for the orlistat treatment may be attributed to the minimal elimination of labeled material from the earthworm in the depuration phase while for carbamazepine the fast elimination of 0.14 d –1 can account for the smaller BCF of 2.21. The BCFs increase in a similar order to the increase in the log octanol–water partition coefficient ( K ow ) for the respective compounds, supporting previous research that has suggested that the degree of hydrophobicity has a key role to play in the uptake of pharmaceuticals into organisms (e.g., Ashauer et al 33 ).…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…The relatively large BCF of 51.5 for the orlistat treatment may be attributed to the minimal elimination of labeled material from the earthworm in the depuration phase while for carbamazepine the fast elimination of 0.14 d –1 can account for the smaller BCF of 2.21. The BCFs increase in a similar order to the increase in the log octanol–water partition coefficient ( K ow ) for the respective compounds, supporting previous research that has suggested that the degree of hydrophobicity has a key role to play in the uptake of pharmaceuticals into organisms (e.g., Ashauer et al 33 ).…”
Section: Resultssupporting
confidence: 81%
“…A first-order one-compartment model was used to estimate the uptake and depuration rates for each test compound from pore water. The toxicokinetic model, as described in eq 1, was fitted to measured internal earthworm concentration data and kinetic bioconcentration factors (BCFs) were then calculated based on principles outlined by Ashauer et al 32,33 Parameter estimation was carried out in OpenModel (v 1.01; University of Nottingham, 2008; ):where t is time (h), k in is the uptake rate constant (L/(kg d)), C water is the concentration in the pore water (Bq/L), k out is the depuration rate constant (d –1 ), and C organism is the concentration in the organism (Bq/kg).…”
Section: Materials and Methodsmentioning
confidence: 99%
“…Uptake rate constants for small aquatic invertebrates seem to be mainly diffusion driven and dependent on the physicochemical properties as well as on the individual test species, whereas no simple relationship exists between elimination rate constants and hydrophobicity. 30,31,63,66,73,74 We have shown that aside from prochloraz, azole BTPs were formed at low concentrations and most biotransformation reactions did not take place at the active moiety, indicating that the antifungal activity as well as the CYP inhibitory capacity of azoles is preserved. This can be of concern for organisms that are exposed to chemical mixtures containing an azole fungicide, as azoles might influence the bioaccumulation potential of other chemicals by inhibiting the CYP catalyzed biotransformation reactions.…”
Section: Environmental Science and Technologymentioning
confidence: 95%
“…The wide suite of chemicals analyzed in the Ashauer et al study 13 demonstrates that the minimized design is a fairly robust way to estimate BCFs with limited laboratory effort as all of the data fit very well to the 1:1 line. Specifically for the Ashauer et al, 2010 data set the slope of the regression line was significantly different from zero (p = < 0.0001) and thus showed a significant relationship between the two methods for calculating BCFs (SI Figure 1).…”
Section: ■ Resultsmentioning
confidence: 96%